The Impact of Service Quality through Customer Satisfaction on Customer Loyalty - Ishak Sagala; Yuniman Zebua; Abd Halim (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
The research aims to recognize the impact of the quality of service through customer satisfaction that is given by the employees of the customer loyalty at UD. Keraton Workshop and its influence on customer loyalty at UD. Keraton Workshop. Data processing techniques using SPSS data analysis. The population in this study are customers or buyers at UD. The Jepara Jati Palace Workshop, which is located in Labuhanbatu. The sample collection technique used is probability sampling by referring to random sampling incidents, the number of samples used is 100 people who shop at UD. Jepara Jati Palace Workshop. The study led to the conclusion the quality of service and customer satisfaction is impacted by partial towards Customer Loyalty is reviewed by Sig. <0.05 for both variables and in terms of the comparison of the value of t count and t table is t table <of t count so that Service Quality and Customer Satisfaction have a positive impact on Customer Loyalty. Looking at the results of models 1 and 2, it can be seen that the direct impact given by the service quality variable on customer loyalty is 0.341 and the indirect effect of service quality through customer satisfaction on customer loyalty is 0.252